Scale-up of hydrogen and ethanol co-production by an engineered Escherichia coli. (15th September 2021) - Lopez-Hidalgo, Angel M.; Balderas Hernandez, Victor E.; De Leon-Rodriguez, Antonio
Graphical abstract: Highlights: Redirection of carbon flux improves up to 70% and 167% the H2 and EtOH production. H2 and EtOH co-production by an engineered E. coli is scale-up. Yields of H2 and EtOH are similar at all the evaluated scales. Abstract: In this work, the scale-up from 0.01 to 10 L process for the co-production of hydrogen (H2 ) and ethanol (EtOH) by a genetically engineered Escherichia coli that utilizes hemicellulosic hydrolysates from wheat straw pretreated (WSP) as substrate is presented. Co-production of biofuels was performed through the redirection of carbon-flux to ethanol by deleting ldhA (D-lactate dehydrogenase) and frdD (fumarate reductase) genes in an H2 -overproducer strain ( E. coli WDH). Resulting strain, E. coli WDH-LF (Δ hycA Δ frdD Δ ldhA ), increased up to 70% and 167% the H2 and EtOH production from glucose compared with the parenteral strain. Using WSP as substrate, the yields of H2 and EtOH remained constant at all the evaluated scales. In 10 L bioreactors, the production parameters such as maximum production, production rate and yield were 5, 603.0 ± 233.5 mL H2 /L, 41.4 ± 4.0 mL H2 /L/h, 342.7 ± 14.3 mL H2 /g TRS, 7.90 ± 0.28 g EtOH/L and 0.48 ± 0.01 g EtOH/g TRS, respectively. The results demonstrate the potential of the co-production of H2 and EtOH at different production scales by the engineered E. coli strain using lignocellulosic biomass as feedstock, such as wheat straw hydrolysates.